Peran Guru Pendidikan Pancasila dan Kewarganegarean dalam Menanamkan Civic Disposition di Bangku Peserta Didik - Yuliana Ngewi; Maria Rosalinda Dhone; Maria Trisanti Watu; Yasinta Lusi; Patrisia Serlinda Meo; Maria Melania Ito (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2025)
Education plays a crucial role in shaping an individual's personality and character, including through character education that instills moral and ethical values. Character education in Kindergarten (TK) is very important in forming the foundational personality of children, such as responsibility, discipline, and respect for others. Teachers play a key role in instilling civic disposition (citizenship attitude) by integrating Pancasila values into the learning process. This study aims to describe the role of Pancasila and Citizenship Education (PPKn) teachers in instilling civic disposition at TK Peupado Malanuza. The method used is a descriptive qualitative approach, with data collected through observation and interviews. The results show that teachers implement civic disposition through activities such as making a Garuda eagle collage, singing the national anthem, and recognizing national symbols, which aim to instill Pancasila values. Teachers also emphasize discipline through activities such as tidying up toys and working together in group tasks. This study demonstrates that the implementation of civic disposition has successfully shaped the children’s character, instilling discipline, responsibility, and love for the country. For sustainability, teachers need to conduct evaluations and involve parents in supporting the values taught.